A district confidential enquiry into deaths due to asthma. Issue 11 (November 1993) - Wareham, N J; Harrison, B D; Jenkins, P F; Nicholls, J; Stableforth, D E
Abstract : BACKGROUND–The aim was to establish a continuing district based confidential enquiry into deaths from asthma. METHODS–A confidential enquiry was conducted in an English health district. Subjects comprised 24 residents of the Norwich health district aged between 16 and 65 years who had died between 1988 and 1991 with asthma as the principal cause of death. RESULTS–Twenty one of the patients (88%) died away from hospital. Overall the routine asthma management was appropriate in all respects in only four patients. In five cases the drug treatment was considered inappropriate, in 10 cases (42%) there was no written evidence that the patient had received advice and education, and only six cases had a written management plan. In 17 patients (71%) the fatal attack of asthma developed rapidly (in under three hours). The medical care during the final attack was found to have been inappropriate in six cases. Seventeen cases (71%) had psychological or social factors that were considered to have been of potential importance. CONCLUSIONS–This study has shown the feasibility of organising a confidential enquiry into asthma deaths within a health district. The distinguishing features of such an enquiry are that it is continuing, that the quality of care given to those patients who died is compared against a recognised standard, and that there is a structured system for feeding back the conclusions of the enquiry to the local medical community.